Short-term treatment with a gonadotropin-releasing hormone antagonist, cetrorelix, in rheumatoid arthritis (AGRA): a randomized, double-blind, placebo-controlled study. (January 2014) - Kåss, AS; Førre, ØT; Fagerland, MW; Gulseth, HC; Torjesen, PA; Hollan, I
<x xml:space="preserve">Abstract</x> Objectives: Gonadotropin-releasing hormone (GnRH) stimulates immune responses; therefore, antagonizing GnRH with cetrorelix may have anti-inflammatory effects. The aim of this study was to assess short-term cetrorelix therapy in rheumatoid arthritis (RA) patients. Method: In this proof-of-concept, randomized, double-blind study involving 99 patients with active, long-standing RA, 48 patients received subcutaneous cetrorelix (5 mg/day on days 1 and 2; 3 mg/day on days 3–5) and 51 received placebo. The primary end-point was the change in the 28-joint Disease Activity Score based on C-reactive protein (DAS28-CRP) by day 5, when the greatest GnRH suppression was anticipated. Secondary end-points included the change in tumour necrosis factor (TNF)-α, and achievement of American College of Rheumatology (ACR) responses and DAS28-CRP < 2.6 by day 5. Patients were followed up on days 10 and 15. Results: By day 5, DAS28-CRP was non-significantly reduced by 0.82 in the cetrorelix group compared to a 0.57 reduction in the placebo group (p = 0.091), TNF-α (log pg/mL) was significantly reduced in the cetrorelix group compared with the placebo group [0.55, 95% confidence interval (CI) 0.08–1.01, p = 0.023], and more patients on cetrorelix achieved ACR20 responses (40% vs. 18%, p = 0.015) and DAS28-CRP < 2.6 (13% vs. 0%, p = 0.009). Inflammatory markers increased towards baseline levels after withdrawal of treatment. Rates of adverse events were similar in both groups. Conclusions: Although there was no significant difference in the primary end-point between groups, antagonizing GnRH led to significant improvements in key secondary end-points. Thus, GnRH antagonists may have rapid anti-inflammatory effects in RA, already occurring within 5 days. The data suggest a novel mode of action for TNF-α inhibition in RA, and potentially in other autoimmune diseases.